Pengenalan dan Evaluasi Eco-Detergen Ramah Lingkungan bagi Pondok Pesantren Nurun Nabi Al-Islami Desa Bandar Khalipah, Deli Serdang - Dhiau Rahman Fikri; Lailatul Husna Lubis (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Household waste has become a significant cause of environmental issues. In addition to solid waste such as plastic, cardboard, and leftover food visible floating on the surface of rivers, large amounts of domestic liquid waste also contribute to river pollution. This has become a severe problem in many major cities in Indonesia, such as Medan, Surabaya, Bandung, Jakarta, and Palembang. Bandar Khalipah Village is among the areas in Medan where its river is starting to be polluted by detergent waste. The Islamic Boarding School was chosen to implement this activity because traditional boarding schools still require students to wash clothes independently. This activity aims to increase public understanding and awareness of the importance of environmental preservation by using environmentally friendly detergents. The stages carried out in implementing activities are the preparation, implementation, and program evaluation stages. The results indicate increased public knowledge about environmentally friendly detergents and active participation in implementing these practices at home. Before the socialization, 65% of participants needed help understanding the technique of making eco-detergent. After the socialization, a good level of understanding was achieved, with 95% of participants successfully mastering the technique of making eco-detergent. The implication is an increased awareness among the public about the importance of environmental conservation and reducing the negative impact of detergents on river ecosystems. Socialization and training programs can be concrete steps in overcoming environmental pollution problems at the local level. Through this effort, the community can continue to adopt sustainable practices to keep the surrounding environment clean and reduce the negative impacts of using conventional detergents.